Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kinerja Karyawan Catering Misshealthy Medan - Naza, Fikri; Irwadi, Irwadi; Robin, Robin (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to examine the influence of occupational safety and health on employee performance productivity at Misshealthy catering in Medan. The research employs a descriptive correlational approach with a non-probability sampling technique due to the relatively small population size. Data were analyzed using multiple linear regression to assess the effect of each independent variable on the dependent variable. The results show that occupational safety has a significant partial effect on employee productivity, while occupational health does not have a statistically significant effect. However, both variables simultaneously have a significant influence on performance productivity. Therefore, improving workplace safety is an important factor in enhancing employee productivity in this catering work environment.